DIRECTIONS OF TECHNOLOGICAL AND DEVELOPMENT REGULATORY AND LEGAL INSTRUMENTS OF THE ORGANIZATION ENVIRONMENTAL ACTIVITY IN UKRAINE: Array - Teliura, N. (Municipal economy of cities. Series: «Economy science», 2021)
One of the main tasks of the environmental industry is innovation, which is now the key to technological progress. Technological and organizational-economic tools, especially in terms of nature management, environmental assessment and entrepreneurship, are aimed primarily at implementing effective, efficient measures aimed at overcoming the deep environmental crisis and ensuring conditions for sustainable development of the state. Technological and organizational-economic mechanisms of greening is a set of organizational forms and economic levers, the interaction of which allows to ensure the implementation of a recurring process aimed at improving the economic and environmental efficiency of social production and stimulating environmental measures. Green (eco-) entrepreneurship is an alternative vision of growth and development. It is necessary to rethink the theoretical approaches and clearly clarify the essence of the organizational and economic mechanism of sustainability of eco-enterprises for its effective formation and implementation of further research in this area. These breakthroughs are expected to lead to significant transformational changes in the functioning of society. These achievements promise significant social and economic benefits, increased efficiency and increased productivity in many areas. Innovations, including technological and organizational-economic tools focused on the collection, processing and analysis of vast arrays of information science data, will have implications for countless areas of research and development. An innovative methodological approach to the definition and justification of priority management technological and organizational and economic decisions for MAI, allows to involve experts in environmental, urban, social, economic direction of municipal authorities of a particular settlement, industrial, residential and military facilities, to justify management decisions environmental safety of settlements, etc. The advantages of the methodological approach include - the ability to link to a single algorithm to justify the solution of data that differ in content (ecological, biological in higher aquatic plants, urban, social and economic) and in the form of presentation (data of direct measurements, statistical and forecast estimates) to develop a single proposal for the application of modern management in practice.